CHARACTERISTICS OF NUMBER SENSE: AN EXPLORATION IN JUNIOR HIGH SCHOOL STUDENTS' ARITHMETICS PROBLEM SOLVING - Nailul Authary; Fitriyasni Fitriyasni; Nurkhaira Nurkhaira (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2024)
Number sense of the child has built up since early childhood. Number sense is crucial need to solving mathematics problems. Regarding the component of some number sense in kindergarten student will help teachers design the appropriate instructional learning of mathematics in schools. Purpose of this reasearch is is investigated thecertain number sense characters through arithmetic. The number sense character study number sense component investigated by the understanding of the numbers meaning, number relations and numbers magnitude. All three characters are investigated through arithmetic question of the test. In this research, number sense component investigated by the understanding of the numbers meaning, number relations and numbers magnitude. The results derived from the answers worksheets and interviews were analyzed based on qualitative data. The results of the study showed number of early childhood number sense is (1) the understanding of the numbers meaning in use concrete objects representation of specific numbers, (2) number relations is making sequencing starting from the smallest (quantity) to the greatest, and (3) numbers magnitude that the understanding begins with recognizing the same number. Further distinguishing different number and choose a bigger number